تطبيقات لاستخدام نظام البريد الإلكتروني في الإدارة الإلكترونية - هاشم, قيس (Journal of Economics and Administrative Sciences, 2012)
This age and the third millennium is the dominance of information technology on most of the administrative work in the developed world and the need for the so-called electronic marketing- and need our developing society to the development of our work to transform the traditional management and routine of it to the electronic management in order to save effort, time and cost They are the backbone speed to complete the work, The principle applications of electronic management to achieve the maximum possible benefit from the implementation of the administrative work of the society and institutions and the private sector the government in the state. The use of electronic management makes us safe from falling into the trap of hindrances and obstacles of the old administration, as described in detail in this research to overcome the challenges and address the technical obstacles and non-technical ones.Designed electronic mail system as described in the research because it represents the service and fill a large part in the field of electronic administration, this system is designed in a language oracle is the largest language for programming distributed databases on the way to apply to university institutions, scientific and academic as more scientific than other institutions as can make the amendment thereto, and add some details to be appropriate and the other shown more in research and can also be an interconnected network between institutions electronically by this system.In addition to the show, the system has the security of a comprehensive range of users and system administrators of intrusions and tampering and unauthorized access to him, we can deduce from the idea of ​​research that can design new systems to serve the electronic management system such as personnel and human resource management and accounting system and other systems, under the principle of distributed database.